A systematic approach for optimization of an algal biorefinery using fuzzy linear programming - Ubando, Aristotle T. (Animo Repository, 2012)
In order to efficiently convert microalgae into value added products, a sustainable integrated algal biorefinery is needed. Generally, conversion of microalgae into biofuel involves several processing steps: cultivation, harvesting, dewatering, drying, oil extraction, and biofuel production. One of the main challenges in designing and optimizing an integrated algal biorefinery is determining the configuration which meets the requirements for key outputs as well as environmental and resource limits. In this work, a systematic fuzzy linear programming (FLP) approach for design and optimization of an integrated algal biorefinery which considers water footprint, land footprint, and carbon footprint is presented. A hypothetical case study is presented to illustrate the proposed approach. © 2012 Elsevier B.V.